Prune Belly Syndrome - Koyye Ravindranath Tagore; Asok Kumar S. Ramineni; A. R. Vijaya Lakshmi; Bhavani N. (Case Reports in Pediatrics)
Prune belly syndrome is a rare congenital disorder of the urinary system, characterized by a triad of abnormalities. The aetiology is not known. Many infants are either stillborn or die within the first few weeks of life from severe lung or kidney problems, or a combination of congenital anomalies.